1996
DOI: 10.1159/000106845
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium and Alzheimer's Disease: Review of Possible Pathogenic Mechanisms

Abstract: Chronic exposure to aluminium (Al) remains a controversial possible cause of sporadic forms of Alzheimer''s disease (AD). This article reviews the evidence that once Al enters the brain and individual brain cells, it may be involved in three pathological processes: (1) the production of abnormal forms of tau leading to the formation of cellular neurofibrillary tangles and neuropil threads; (2) the processing of the amyloid precursor protein, resulting in the formation of β-amyloid deposits and senile plaques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Much of the evidence that Al is a cause of AD is circumstantial and controversial [21]. Epidemiological studies [77,120,133] have found little correlation between environmental Al and AD.…”
Section: Aluminiummentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the evidence that Al is a cause of AD is circumstantial and controversial [21]. Epidemiological studies [77,120,133] have found little correlation between environmental Al and AD.…”
Section: Aluminiummentioning
confidence: 99%
“…In addition, out of 13 studies, in which gross brain tissue has been analysed for Al, 9/13 found enhanced levels in AD brain, while 4/13 found no significant differences compared with control brains [34]. The significance of enhanced Al levels in brain is also unclear since damaged brains may accumulate Al [21]. The presence of Al may also be linked to the formation of SP and NFT.…”
Section: Aluminiummentioning
confidence: 99%
See 1 more Smart Citation
“…Al was also found to be a major causative factor in the development of dialysis encephalopathy [5,6]. This element has been proposed as a contributor to the pathogenesis of serious neurological disorders such as Alzheimer's disease, amyotrophic lateral sclerosis and parkinsonism-dementia of Guam [7][8][9][10][11]. In these neurodegenerative diseases, the pathologic features that they share include abnormal phosphorylation of neuronal cytoskeletal proteins and the abnormal deposition of these proteins in neurons.…”
mentioning
confidence: 99%
“…Although aluminum certainly forms the basis of dialysis dementia, the role of this nonessential element in the etiology of Alzheimer's disease is more controversial ( 4 ). It has been claimed that chelation of aluminum with deferoxamine may ameliorate this disease (24).…”
mentioning
confidence: 99%